2005
DOI: 10.1002/ejoc.200500431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Host–Guest Hydrogen Bond on the Inclusion of Alcoholic Guests in the Host Cavities of Cholamide

Abstract: Fifty eight inclusion crystals of cholamide (CAM) with aliphatic alcohols have been systematically investigated by X‐ray crystallography. The host frameworks of the inclusion crystals can be categorized into three structural types: bilayer, herringbone, and crossing structures. Most of the guests are included in bilayer structures, which can be further divided into four sub‐types. The host frameworks isomerize depending on the size and shape of the guest molecules. This dependence is clearly evaluated by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
1
27
1
Order By: Relevance
“…This suggests that for the compounds with longer alkyl side chains, the intermolecular bile acid–bile acid interactions were preferred over the bile acid–solvent interactions. The hydroxyl and amide groups were fully utilized in forming the intermolecular O−H⋅⋅⋅O and N−H⋅⋅⋅O hydrogen bonds to give a typical ordered 1D bilayered structure (Figure S7, Supporting Information) . The Hirshfeld surface analysis for crystal structures of all compounds LCA 1 – CA 9 indicated that these bilayers form a compact 3D crystal lattice through a high percentage of H⋅⋅⋅H interactions (Table S6 and Figures S9–S17, Supporting Information).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This suggests that for the compounds with longer alkyl side chains, the intermolecular bile acid–bile acid interactions were preferred over the bile acid–solvent interactions. The hydroxyl and amide groups were fully utilized in forming the intermolecular O−H⋅⋅⋅O and N−H⋅⋅⋅O hydrogen bonds to give a typical ordered 1D bilayered structure (Figure S7, Supporting Information) . The Hirshfeld surface analysis for crystal structures of all compounds LCA 1 – CA 9 indicated that these bilayers form a compact 3D crystal lattice through a high percentage of H⋅⋅⋅H interactions (Table S6 and Figures S9–S17, Supporting Information).…”
Section: Resultssupporting
confidence: 83%
“…Considering that the formation of bilayered structures, involving the functional groups in the head (hydroxyl groups) and tail (carboxylic acid groups or their derivatives) of the steroidal backbone, is typical for bile acid derivatives in the solid state, it is reasonable to assume that similar structures exist also in the semi‐solid or gel states. In the case of CA and its derivatives, the inter‐bilayer interactions are reinforced by hydrogen bonds between the hydroxyl groups at positions 7α and 12α (Table S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because one additional hydrogen bond donor acts as a hook for catching a guest molecule with hydrogen bond acceptor. Ib forms the same bilayer structure as Ia, with almost the same cavity dimensions [ Figure 2(d) [38][39][40][41][42]. The hydroxyl groups of the guest molecules are linked between two cyclic hydrogen bonding networks [ Figure 3(g)].…”
Section: Amide Ester and Alcohol Hostsmentioning
confidence: 99%
“…In other words, supramolecular isomerism of the host frameworks can be understood in terms of guest size. Since the supramolecular isomerism of the host frameworks is closely related to how well the guest molecules and the host cavity fit together, 53,54 the volumes of the guest molecules and the host cavities were calculated, as summarized in Table 3. The packing coefficient of the host cavities (PC cavity ), which is the parameter used to estimate the steric fit between the guest molecule and the host cavity, 53 can be determined from their volumes.…”
Section: 6(3)mentioning
confidence: 99%